2010
DOI: 10.1007/s10562-010-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation into the Rearrangement of Lactone into Methacrylic Acid over Phosphomolybdic Acid Catalyst

Abstract: The rearrangement of 3-methyl-2-oxetanone (lactone) into methacrylic acid has been explored using DFT methods. Calculations were performed for (i) intramolecular, (ii) lactone-lactone and (iii) water and phosphomolybdic acid catalyzed conversions. The water and acid surface catalyzed route exhibited the lowest activation barrier (156 kJ mol -1 ) of the three reaction pathways and overall is slightly endothermic (DH f = 37 kJ mol -1 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…This intimates that lactone is a precursor to methacrylic acid formation. Nguyen et al have shown that the lactone rearranges into methacrylic acid via catalysis by water and acid [38]. It is proposed that lactone rearranges to methacrylic acid under normal reaction conditions of high pressures but is instead isolated in this work due to the molecular flow regime.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This intimates that lactone is a precursor to methacrylic acid formation. Nguyen et al have shown that the lactone rearranges into methacrylic acid via catalysis by water and acid [38]. It is proposed that lactone rearranges to methacrylic acid under normal reaction conditions of high pressures but is instead isolated in this work due to the molecular flow regime.…”
Section: Discussionmentioning
confidence: 88%
“…However propene forms over some of the Group 1 salts (but not over Group 2 compounds) and methacrylic acid is also seen over a single Group 2 phosphomolybdate: BaH[PMo 12 O 40 ]. It has been shown that lactone is a precursor to methacrylic acid, and the lactone is prevented from rearranging into methacrylic acid due to the unique low-pressure, steady-state, molecular flow conditions used in TPRS [38]. Interestingly, the cesium series of phosphomolybdates were the compounds that did not produce any lactone or acetic acid, and only minimal CO 2 , but were very active toward methacrolein formation.…”
Section: Products From Tprsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to declining methacrolein pressures within the Knudsen cell as temperature increases. Negative activation energies may indicate competing reactions (e.g., formation of β-lactone [29]), secondary methacrolein reactions on the catalyst surface (e.g., dimerization), or the formation of metastable states. Activation energy distributions in the high-temperature region, for all catalysts are investigated in this paper, and have been the focus of previous analyses [2,10].…”
Section: High-temperature Average Rate-parameters For Methacrolein Fmentioning
confidence: 99%
“…Methacrylic acid is commonly reported from isobutane oxidation, but is not observed. It has been shown that lactone is a precursor to methacrylic acid, and the lactone is prevented from rearranging into methacrylic acid due to the unique low-pressure, steady-state, molecular flow conditions used in TPRS [65].…”
Section: Products Observed With Tprsmentioning
confidence: 99%